Using subtitles for the deaf and hard of hearing as an innovative pedagogical tool in the language class - Talaván, Noa (International Journal of English Studies, 2019)
The present article describes a didactic proposal based on the use of an audiovisual translation and accessibility mode as a pedagogical tool: subtitles for the deaf and hard of hearing (SDH). When students create SDH for a pre-selected clip within a well-structured task, they are enhancing integrated skills, especially in the form of written production (of the subtitles), listening comprehension (of the original), and lexical creativity (through the condensation of the original message in the form of subtitles and the description of paralinguistic elements). A project undertaken with online students to assess the potential benefits of SDH has acted as a preliminary study to back up the didactic proposal presented herein. The main data gathered from this experience offers a reference for future practice and research in this field, since it confirms previous assumptions on the validity of subtitling as a pedagogical tool to improve foreign language learning skills.